P183 Osteitis condensans ilii or axial spondyloarthritis: a diagnostic challenge!. (26th April 2021) - Saeed, Sadaf; Jamal, Muhammad Safwan; Ostry, Dave; Robinson, Graham; Sengupta, Rajiv
Abstract: Background/Aims   Osteitis condensans ilii (OCI) is a rare cause of chronic non-inflammatory axial lower back pain. It has become an important differential diagnosis of axial spondyloarthritis. Bone marrow oedema can be present in 48% of patients. Although 'aunt minnie' appearance on MRI is pathognomonic, specialised imaging like SPECT/PET CT can be considered in difficult cases to confirm the diagnosis. We reviewed case notes of patients with incidental diagnosis of OCI on imaging and followed their clinical progression to see if the diagnosis was modified later. Methods   Retrospective radiological database analysis was performed to find imaging reported as OCI or osteitis from 2015-2020. Electronic patient records were analyzed and data was compiled through Microsoft Excel. Results   Data from 24 patients was reviewed. Most patients were females (91.7%), with a median age of 43 years (range 19-79 years). CT and MRI were the chief modalities of imaging (46% and 38% respectively) while 20% had plain x-rays of the pelvis. The main indications for imaging were pelvic or hip girdle pain (58.3%), cancer surveillance (25%), abdominal pain (6%), and infection (6%). 20% had an underlying rheumatological diagnosis of which 8% had spondyloarthritis. 12.5% of patients had seronegative features of spondyloarthritis and 8.3% were HLA B27 positive. Approximately 40% of patients were seen by the Rheumatology team for further assessment after imaging and 12.5% of patients were diagnosed with axial spondyloarthritis and remained under follow-up. Conclusion   OCI can mimic sacroiliitis on imaging. Although only a minority of patients with OCI reported on initial imaging were subsequently diagnosed with axial spondyloarthritis, thorough clinical assessment and multidisciplinary discussion can reduce the chance of a missed axial spondyloarthritis diagnosis. Further large-scale studies are required to find the exact incidence of spondyloarthritis in patients with imaging features of OCI. Disclosure   S. Saeed: None. M. Jamal: None. D. Ostry: None. G. Robinson: None. R. Sengupta: None.